147k views
3 votes
Give the equation of the circle that has a diameter with endpoints G(-6, — 3) and
R(-6,-8).

User Amr Magdy
by
6.1k points

1 Answer

4 votes

Circle Equations

Generally, the equation of a circle is organized like this:
(x-h)^2+(y-k)^2=r^2, where (h,k) is the centre and r is the radius.

Solving the Question

We're given the endpoints of the diameter:
(-6,-3) and
(-6,-8).

First, we can find the centre of the circle by finding the midpoint of these two endpoints.


midpoint=((x_1+x_2)/(2),(y_1+y_2)/(2))

Plug in the points:


midpoint=((-6+-6)/(2),(-3+-8)/(2))\\\\midpoint=(-6,(-11)/(2))

Therefore, the centre of the circle is
(-6,(-11)/(2)). Plug this into the general equation:


(x-h)^2+(y-k)^2=r^2\\\\(x-(-6))^2+(y-(-(11)/(2)))^2=r^2\\\\(x+6)^2+(y+(11)/(2))^2=r^2

To find the radius of the circle, we can calculate the distance between the centre and one of the given endpoints:


d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2

Plug in the centre and one of the endpoints:


d=\sqrt{(-6-x_1)^2+((-11)/(2)-y_1)^2}\\d=\sqrt{(-6-(-6))^2+((-11)/(2)-(-3))^2}\\d=\sqrt{(-6+6)^2+((-11)/(2)+3)^2}\\\\d=√((0)^2+(-5.5+3)^2)\\\\d=√((0)^2+(-2.5)^2)\\\\d=\sqrt{(0)^2+(-(5)/(2))^2}\\\\d=\sqrt{0+(25)/(4)}\\d=\sqrt{(25)/(4)}\\\\d=(5)/(2)

Therefore, the radius of the circle is
(5)/(2). Plug this into the general equation:


(x+6)^2+(y+(11)/(2))^2=r^2\\\\(x+6)^2+(y+(11)/(2))^2=((5)/(2))^2\\\\(x+6)^2+(y+(11)/(2))^2=(25)/(4)

Answer


(x+6)^2+(y+(11)/(2))^2=(25)/(4)

User Mervin Hemaraju
by
5.9k points